Pengaruh Pemberian Jus Kurma Dan Madu Terhadap Peningkatan Produksi Asi Pada Ibu Nifas Di PMB Fitri Chandra Tumpang - Vinanda Dzurriyyatun Nisa; Tut Rayani Aksohini Wijayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Breast milk (ASI) is the primary and most essential source of nutrition for infants, playing a crucial role in their growth and development. Various studies have shown that the consumption of natural, nutrient-rich foods can help improve breast milk production. One such combination is date and honey juice, which is rich in carbohydrates, vitamins, and minerals that stimulate the production of prolactin and oxytocin—two key hormones involved in lactation. Dates are high in iron, calcium, and fiber, while honey contains enzymes and antioxidants that support the mother's metabolic health during breastfeeding. This study aims to evaluate whether the administration of date and honey juice affects the increase in breast milk production among postpartum mothers and its impact on the weight of newborns aged 0–7 days. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 10 postpartum mothers. Participants were given date and honey juice daily for seven consecutive days, and changes in the infants’ weight were measured before and after the intervention as an indirect indicator of breast milk production success.